Kinected Browser: Depth Camera Interaction for the Web - Liebling, Dan; Morris, Meredith Ringel (Proc. 2012 ACM Conference on Interactive Tabletops and Surfaces, 2012)
Interest in and development of gesture interfaces has recently exploded, fueled in part by the release of Microsoft Corporation's Kinect, a low-cost, consumer-packaged depth camera with integrated skeleton tracking. Depth-camera-based gestures can facilitate interaction with the Web on keyboard-and-mouse-free and/or multi-user technologies, such as large display walls or TV sets. We present a toolkit for bringing such gesture affordances into modern Web browsers using existing Web programming methods. Our framework is designed to enable Web programmers to incrementally add this capability with minimum effort by leveraging Web standard DOM structures and event models. We describe our framework's design and architecture, and illustrate its usability and versatility.